Alpha-Soluble NSF Attachment Protein Prevents the Cleavage of the SARS-CoV-2 Spike Protein by Functioning as an Interferon-Upregulated Furin Inhibitor - Jinliang Wang; Jie Luo; Zhiyuan Wen; Xinxin Wang; Lei Shuai; Gongxun Zhong; Chong Wang; Ziruo Sun; Weiye Chen; Jinying Ge; Renqiang Liu; Xijun Wang; et al. (mBio, 2022)
ABSTRACT Loss of the furin cleavage motif in the SARS-CoV-2 spike protein reduces the virulence and transmission of SARS-CoV-2, suggesting that furin is an attractive antiviral drug target. However, lack of understanding of the regulation of furin activity has largely limited the development of furin-based therapeutic strategies. Here, we find that alpha-soluble NSF attachment protein (α-SNAP), an indispensable component of vesicle trafficking machinery, inhibits the cleavage of SARS-CoV-2 spike protein and other furin-dependent virus glycoproteins. SARS-CoV-2 infection increases the expression of α-SNAP, and overexpression of α-SNAP reduces SARS-CoV-2 infection in cells. We further reveal that α-SNAP is an interferon-upregulated furin inhibitor that inhibits furin function by interacting with its P domain. Our study demonstrates that α-SNAP, in addition to its role in vesicle trafficking, plays an important role in the host defense against furin-dependent virus infection and therefore could be a target for the development of therapeutic options for COVID-19. IMPORTANCE Some key mutations of SARS-CoV-2 spike protein, such as D614G and P681R mutations, increase the transmission or pathogenicity by enhancing the cleavage efficacy of spike protein by furin. Loss of the furin cleavage motif of SARS-CoV-2 spike protein reduces the virulence and transmission, suggesting that furin is an attractive antiviral drug target. However, lack of understanding of the regulation of furin activity has largely limited the development of furin-based therapeutic strategies. Here, we found that in addition to its canonical role in vesicle trafficking, alpha-soluble NSF attachment protein (α-SNAP) plays an important role in the host defense against furin-dependent virus infection. we identified that α-SNAP is a novel interferon-upregulated furin inhibitor and inhibits the cleavage of SARS-CoV-2 spike protein and other furin-dependent virus glycoproteins by interacting with P domain of furin. Our study demonstrates that α-SNAP could be a target for the development of therapeutic options for COVID-19.